2000
DOI: 10.1161/01.str.31.12.2920
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Tissue Plasminogen Activator for Acute Ischemic Stroke

Abstract: Background and Purpose —In the United States, tissue plasminogen activator (tPA) was approved for treatment of acute ischemic stroke in 1996. Its use has only recently been approved in Canada. We sought to evaluate the safety, feasibility, and efficacy of treatment in a Canadian hospital setting. Methods —A combined retrospective and prospective review is presented of 46 consecutive patients treated with intravenous tPA at our hospital with a treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 21 publications
8
34
0
3
Order By: Relevance
“…3), and was similar to rates in other reported series. [26][27][28][29][30][31][32][33][34][35][36] Serious adverse events occurred in 75 (6.6%) of the patients (95% CI 5.2%-8.2%) ( Table 3). Of the 52 (4.6%) who had a symptomatic intracranial hemorrhage, 39 (75%) died in hospital.…”
Section: Resultsmentioning
confidence: 99%
“…3), and was similar to rates in other reported series. [26][27][28][29][30][31][32][33][34][35][36] Serious adverse events occurred in 75 (6.6%) of the patients (95% CI 5.2%-8.2%) ( Table 3). Of the 52 (4.6%) who had a symptomatic intracranial hemorrhage, 39 (75%) died in hospital.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has also been observed in intravenous tPA studies when the 3-hour limit was close. 18,28 Demographic factors such as sex and age did not influence the time delay to treatment. Patients who were already familiar with the signs and symptoms of stroke because of previous cerebrovascular events did not arrive faster in the ED of our stroke center.…”
Section: Discussionmentioning
confidence: 96%
“…12,14,[17][18][19][20][21] It has also been shown that educational programs for both the public and physicians increase the number of patients arriving at the hospitals within the time limits for thrombolysis. 22 In US stroke centers, up to 59% of the patients who presented within 24 hours of symptom onset arrived within 3 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22] Studies elsewhere have demonstrated that community and academic hospitals can deliver tPA effectively. 20,[23][24][25][26][27][28][29][30] However, numerous internal and external barriers exist to expanding delivery more broadly in patients with stroke. 31,32 Work published elsewhere found that a combination of community and professional education increased thrombolytic use in patients with stroke, from a preintervention rate of 2.2% to a postintervention rate of 11.3% (p = 0.007), with the data suggesting that the professional education component was the critical element in increasing use.…”
Section: Introductionmentioning
confidence: 99%